Brain-Computer Interfaces for Human-Computer Interaction and Games - Nijholt, Anton; Tan, Desney; Allison, Brendan; Millan, Jose del R; Graimann, Bernhard; Jackson, Melody Moore (Workshop at CHI 2008 Conference on Human Factors in Computing Systems. Florence, Italy., 2008)
In this workshop we study the research themes and the state-of-the-art of brain-computer interaction. Braincomputer interface research has seen much progress in the medical domain, for example for prosthesis control or as biofeedback therapy for the treatment of neurological disorders. Here, however, we look at brain-computer interaction especially as it applies to research in Human-Computer Interaction (HCI). Through this workshop and continuing discussions, we aim to define research approaches and applications that apply to disabled and able-bodied users across a variety of real-world usage scenarios. Entertainment and game design is one of the application areas that will be considered.